A Influência do Pensamento Criativo e dos Estilos de Liderança no Desempenho Gerencial em Startups - Borges, Edson Miguel Graeff (2023)
This dissertation sought to analyze the influence of organizational creative thinking style and the type of leadership on managerial performance in startups. Creative thinking, which converge and diverge, in the creation of ideas, and managerial performance were analyzed, as well as the mediating influence of transactional and transformational leadership in the managerial performance of startups. The research was descriptive and quantitative, through a questionnaire for data collection. The research was carried out cross-sectionally; for that, with the use of a construct, for the structural analysis, through structured equations, with the partial least squares method. The sample was of the intentional type, due to availability, questionnaires were sent to the startups on the Associação Brasileira de Startups (ABStartups) website, which met the criteria of this research proposal. The research found relevant findings: convergent thinking has a positive correlation with transactional leadership; divergent thinking is positively correlated with transactional leadership; divergent thinking has a strong positive correlation with transformational leadership; and there is a positive correlation between convergent thinking and transformational leadership. The findings indicate that managerial performance is positively influenced by convergent and divergent creative thinking, when mediated by transactional and transformational leadership styles. This research contributes to the creativity literature, by using the mediation of creative thinking, with leadership styles, in managerial performance in startups. In the practical part, it can be suggested the use of the type of creative thinking, divergent and convergent, in each moment of the creative process, the style of leadership, sometimes the negotiation and incentives, the transactional leadership, sometimes the motivational and inspiring, the leadership transformational. In social issues, managers, when faced with the negative effects of psychological and emotional factors, as well as with economic-financial issues, both personal and work teams, as well as their own and the startup where they work, can take advantage of these theoretical propositions to solve these important problems, interpersonal and individual.